Study on the Laser Decontamination of Metal Surface at 1064 and 532 nm - Won, Hui-Jun; Jung, Sun-Hee; Jung, Chong-Hun; Seon Choi, Byung; Moon, Jei-Kwon; Lee, Kune-Woo (Asian Journal of Chemistry, 2012)
Type 304 stainless steel is contaminated with CsNO3, Co(NH4)2(SO4)2, CeO2 and Eu2O3. We present the experimental results on decontamination of contaminants attached to type 304 stainless steel surface by coherent light of 1064 nm wavelength and its second harmonic generation occurring at 532 nm derived from a Q-switched Nd:YAG laser. The surface morphology and the relative atomic molar per cent of the specimen surface have been investigated by SEM and EPMA. The decontamination behaviour has been investigated for the variables such as a number of laser shots and fluence. The decontamination behaviour at 532 nm by varying the irradiation angle has also been investigated. The optimum laser fluence at 1064 nm wavelength is found to be 57.3 J/cm2 and 97.7 % of Cs+ ion is removed during 40 laser shots. The optimum application condition at 532 nm wavelength is found to be 13.3 J/cm2 and 30º, respectively. The order of decontamination efficiency at 1064 nm is CsNO3 > Co(NH4)2(SO4)2 > CeO2 > Eu2O3 and at 532 nm is CsNO3 > Co(NH4)2(SO4)2 > Eu2O3 > CeO2.